Analisis Implementasi Tujuh Langkah Menuju Keselamatan Pasien di Ruang Rawat Inap Rumah Sakit - Nisrina Nisrina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Patient safety is an absolute thing in the service of a hospital. Services that promote a sense of security and comfort are the hopes of every patient when receiving health services. However, the high number of unexpected events in health services at hospitals become an indication that the implementation of patient safety management, especially the seven steps towards patient safety, is not running well. The research method in this study was descriptive qualitative. The data collection techniques used were interviews, observation, and documentation study. From this study, it was found that the implementation of patient safety management on the seven steps towards patient safety has been carried out in hospitals, but there are still obstacles that resulted in the implementation that is not being maximized. Improvement efforts should be continued to implement the seven steps program towards patient safety optimally.